Disney Movies and Their Role in Improving Students’ Listening Skills: Film Disney dan Perannya dalam Meningkatkan Kemampuan Mendengarkan Siswa - Winner, Wewen Lady; Taufiq, Wahyu (Indonesian Journal of Education Methods Development, 2024)
English, as an international language, plays a crucial role in global communication, with listening skills being essential for effective learning. However, challenges remain in engaging students in listening comprehension. This study aims to evaluate the use of the Disney movie 'Luca' as a tool for improving listening skills among seventh-grade students at SMPN Tanggulangin. Utilizing a pre-experimental design, 32 students were selected through purposive sampling, with data collected from pretests and posttests. Findings reveal a significant enhancement in listening comprehension post-intervention, evidenced by a p-value of 0.000, indicating that the null hypothesis is rejected. The study demonstrates that incorporating movies into the learning process not only aids in comprehension but also creates a more relaxed and enjoyable learning environment for students. The novelty of this research lies in its focus on integrating popular media into language education, addressing a gap in effective listening instruction. As a result, this study suggests that educators should routinely integrate film technology into language learning to foster better listening skills among students, thereby enriching their educational experience. Highlights: Significant Improvement: The study found a notable enhancement in listening comprehension after using the Disney movie 'Luca' as a learning tool. Engaging Learning Environment: Incorporating movies made the learning process more enjoyable and relaxed for students. Recommendations for Educators: The research suggests integrating film technology into language education to improve students' listening skills consistently. Keywords: Disney movie, listening comprehension, language education, student engagement, educational technology.